Antagonistic action of the composite preparation on the basis of lactic acid bacteria on conditionally pathogenic microorganisms - Голубіцька, В. О.; Суслова, О. С.; Ястремська, Л. С. (Problems of Environmental Biotechnology, 2018)
The antagonistic activity of individual strains of lactic acid bacteria and the bacterial composite preparation created on their basis to conditionally pathogenic microorganisms was studied. It has been shown that the legs of lactic acid bacteria show different levels of inhibition of conditionally pathogenic microorganisms. The antagonistic activity, on the test cultures tested, of the bacterial composite preparation BK-1 is higher, compared to monocultures and a commercial composite comparator – BK-2.